(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Indian naturalism, through various ages and withdifferent degrees, has always relied on the outer aspect of things as a meansand proof of understanding a preexistent inner situation within a cyclic visionof nature. In contrast, in a capillary system, one and the same fluid rises indifferent and connected tubes emphasizing on a linear view of understanding thehuman intervention with nature. The creative acknowledgement of this internaland living connectedness of an inner experience of nature and the visibleworld, by putting it into form, is a characteristic hallmark of Indiannaturalism. It comprises innervations as well as transubstantiation and can beseen palpably depicted in various images and not simply those representingnature.